New species and new records of Belostoma Latreille, 1807 (Insecta: Hemiptera: Belostomatidae) from northeastern Brazil - Stefanello, Fabiano; Azevêdo, Carlos Augusto Silva De (Zootaxa, 2024)
Belostoma zecai Stefanello sp. nov. (Insecta: Hemiptera: Belostomatidae) is described and illustrated based on specimens from the Nascentes do Rio Parnaíba National Park, a protected area in the state of Maranhão, northeastern Brazil. This new species is assigned to the Belostoma fittkaui species group and compared with its congeners. The other four species of the genus, B. amazonum Estévez & Polhemus, 2001, B. foveolatum (Mayr, 1864), B. horvathi Montandon, 1903, and B. ribeiroi De Carlo, 1933, are also recorded from the region. Our findings increase the number of species of Belostoma recorded from Maranhão from 13 to 18, and from northeastern Brazil from 18 to 20.